2007
DOI: 10.1103/physreva.76.032304
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic local operations and classical communication invariant and the residual entanglement fornqubits

Abstract: In this paper, we find the invariant for n-qubits and propose the residual entanglement for n-qubits by means of the invariant. Thus, we establish a relation between SLOCC entanglement and the residual entanglement. The invariant and the residual entanglement can be used for SLOCC entanglement classification for n-qubits.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
0
30
1
Order By: Relevance
“…In 1999, Lukin et al introduced the idea of DDR and showed that in a Λ-type system, the coherent interaction can lead to a splitting of dark states and the emergence of sharp spectral features [36]. Later, it was shown that this novel spectral feature can be characterized as a powerful mechanism for Doppler-free resonance [37,38], group velocity controlling [39,40], coherently control the adiabatic passage [41,42], four-wave mixing [43,44] and high resolution spectroscopy [45,46]. Up to now, different schemes of the DDR have been investigated and also various phenomena induced by the interacting dark resonance have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Lukin et al introduced the idea of DDR and showed that in a Λ-type system, the coherent interaction can lead to a splitting of dark states and the emergence of sharp spectral features [36]. Later, it was shown that this novel spectral feature can be characterized as a powerful mechanism for Doppler-free resonance [37,38], group velocity controlling [39,40], coherently control the adiabatic passage [41,42], four-wave mixing [43,44] and high resolution spectroscopy [45,46]. Up to now, different schemes of the DDR have been investigated and also various phenomena induced by the interacting dark resonance have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-wave mixing process, as one of the interesting and striking nonlinear quantum optical phenomena based on atomic coherence and quantum interference, has been the promising candidates of many groups because of its potential wide applications in quantum single-photon nonlinear optics and quantum information science [1][2][3][4][5][6][7][8][9][10][11]. However, the application of multi-wave mixing is limited by its usual low efficiency [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The field of POVMs is rather large and technical see for example [97,98,99], for now we will content ourselves with a basic functional introduction. The following introduction leans heavily on Nielsen and Chuang [97].…”
Section: Locc and Sloccmentioning
confidence: 99%